Investigation of Thermal Conductivity and Dynamics Viscosity of Green Nanofluids (ZrO2-SiO2) - Ramadhan, Anwar Ilmar; Saptaji, Kushendarsyah; Hendrawati, Tri Yuni; Sari, Alvika Meta; Umar, Efrizon; Aziz, Azmairit; Semendo, Rifqi Putra; Setiawan, Hanif Rama Yuda; Firmansyah, Firmansyah (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
In recent years, research has been directed towards improving the thermophysical properties of single-component nanofluids. Therefore, hybrid or composite nanofluids are developed to improve heat transfer performance. The thermophysical properties of ZrO2-SiO2 nanoparticles suspended in a mixture of water (W) and ethylene glycol (EG) with vol 60:40 or Green Nanofluids for various volume concentrations were investigated. Experiments were performed for volume concentrations of 0.1, 0.2, and 0.3% of green nanofluids at 50, 60, 70, and 80°C. Measurements of thermal conductivity and dynamic viscosity are performed at temperatures ranging from 50-80°C. The highest thermal conductivity of the green nanofluids is obtained at a concentration of 0.3%, and the maximum increase is up to 37.5% higher than the base fluid (EG/W). Meanwhile, evidence from the dynamic viscosity of green nanofluids is affected by concentration and temperature. Furthermore, the green nanofluids behave as a Newtonian fluid in a volume concentration of 0.1-0.3%. In conclusion, the combination of increased thermal conductivity and dynamic viscosity at a concentration of 0.3% has optimal conditions, which has more advantages for heat transfer than at other concentrations.